The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00338-018-1678-x
|View full text |Cite
|
Sign up to set email alerts
|

Marked annual coral bleaching resilience of an inshore patch reef in the Florida Keys: A nugget of hope, aberrance, or last man standing?

Abstract: Annual coral bleaching events, which are predicted to occur as early as the next decade in the Florida Keys, are expected to cause catastrophic coral mortality. Despite this, there is little field data on how Caribbean coral communities respond to annual thermal stress events. At Cheeca Rocks, an inshore patch reef near Islamorada, FL, the condition of 4234 coral colonies was followed over 2 yr of subsequent bleaching in 2014 and 2015, the two hottest summers on record for the Florida Keys. In 2014, this site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
99
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 47 publications
(58 reference statements)
10
99
1
Order By: Relevance
“…The average tissue loss of 21% indicates that stress was a factor, but whether this was reflective of what was happening at the time to wild colonies at the respective sites is unknown. Orbicella faveolata is remarkably resistant to complete mortality (Edmunds ), as recently demonstrated in the Florida Keys during repetitive bleaching events in 2014 and 2015 (Gintert et al ); however, percent coverage of Orbicella spp. across the Florida reef tract has declined significantly since 1998, most likely because of partial mortality (Toth et al ).…”
Section: Discussionmentioning
confidence: 93%
“…The average tissue loss of 21% indicates that stress was a factor, but whether this was reflective of what was happening at the time to wild colonies at the respective sites is unknown. Orbicella faveolata is remarkably resistant to complete mortality (Edmunds ), as recently demonstrated in the Florida Keys during repetitive bleaching events in 2014 and 2015 (Gintert et al ); however, percent coverage of Orbicella spp. across the Florida reef tract has declined significantly since 1998, most likely because of partial mortality (Toth et al ).…”
Section: Discussionmentioning
confidence: 93%
“…However, we argue that it is more likely that shuffling drove this change in region‐wide symbiont dominance given that O. faveolata is well documented to host multiple symbiont genera simultaneously as well as readily shuffle to dominance by D. trenchii during and after bleaching (Kemp et al., ). Long‐term monitoring at UKI1, a reef where O. faveolata is the most abundant coral , revealed that only 4 of 552 tracked colonies (<1%) died during the 2014–2015 bleaching (Gintert et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the response to bleaching in O. faveolata in 2014 and 2015 appears to be different than the prior Keys‐wide mass bleaching event in 2005. This difference may be because the bleaching in 2005 was less severe than 2014 and 2015, owing to less heat stress in 2005 (see Gintert et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Florida demonstrated lower rates of bleaching and mortality by observing more than 4,000 coral colonies of multiple species in the second of successive mass bleaching events (Gintert et al, ). This study suggest broad community level acclimatization because the second bleaching event resulted in moderate impacts despite accrued additional degree heating weeks, which typically tracks closely with bleaching severity (Hughes, Kerry, et al, ).…”
Section: Ecological Signatures Of Acclimatization In Coralsmentioning
confidence: 99%